Response of Wheat to Suboptimal Nitrogen Under Saline Water Irrigation - Kumar, V; Kumar, D (Annals of Arid Zone, 2016)
A micro-plot study on HD 1593 wheat was carried out during 1978-80, in a single-strip plot design with 2 levels of Nand 4 levels of water salinity on a sandy loam soil. Adverse: effect of salinity was greatly manifested on grain and dry matter yield during rainfall deficit year 1979-80. Normal level of N (120 kg) proved optimum at ECi 8 and 12 dS m-1 whilst suboptimal N (72 kg) was significantly superior at ECi 16 dS m-1.